CLOUD COMPUTING AND MODERN FRONTEND DEVELOPMENT IN U.S. CAPITAL MARKETS: A TECHNICAL OVERVIEW - Venkata Raja Ravi Kumar Gelle, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
The integration of cloud computing with modern frontend frameworks in U.S. capital markets represents a transformative shift in financial technology infrastructure. This article explores the convergence of cloud technologies with Angular and React frameworks, examining their impact on market operations, trading systems, and data processing capabilities. The article investigates scalability, security, real-time data processing, and cloud-native architectures, highlighting how these technologies enhance market efficiency, reduce latency, and improve trading platform performance. Through a detailed examination of microservices implementation and container orchestration strategies, this article demonstrates how modern architectural patterns are reshaping financial systems while ensuring regulatory compliance and operational resilience.